THU0382 FACTORS ASSOCIATED WITH POOR WORK OUTCOMES IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS IN SINGAPORE. (June 2019) - Goh, Yihui; Kwan, Yu Heng; Leung, Ying Ying; Fong, Warren; Cheung, Peter
Abstract : Background: Axial spondyloarthritis (axSpA) can lead to significant limitation of mobility and function, resulting in poor work outcomes. 1 Factors associated with poor work outcomes have not been studied in an Asian population. Singapore is an urban Asian city with a low unemployment rate and a healthcare model with heavy emphasis on self-reliance. 2 This socio-cultural context may influence risk factors for poor work outcomes. Objectives: To identify factors associated with poor work outcomes in patients with axSpA in Singapore. Methods: A cross-sectional study was performed in two tertiary centres in Singapore. Patients ≥21 years fulfilling Assessment in Spondyloarthritis International Society (ASAS) 2009 criteria for axSpA were included. We collected social demographics, clinical data, treatment modalities and patient reported outcomes, including the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), EQ-5D index, and Work Productivity and Activity Impairment scale (WPAI:SpA). WPAI:SpA was used to derive scores for presenteeism (reduced productivity while at work), absenteeism (time absent from work), work impairment (combining presenteeism and absenteeism scores) and activity impairment (impairment in activities performed outside of work). Univariable and multivariable linear regressions were used to examine factors associated with presenteeism, absenteeism, work impairment and activity impairment. Results: A total of 156 patients with axSpA were included: 72.4% employed, 80.1% male, 86.5% Chinese, mean age 39.2 (13.0) years, mean disease duration 8.5 (8.9) years. The mean BASDAI was 3.2 (2.0), mean BASFI was 2.1 (2.1), mean EQ-5D was 0.8 (0.1) and mean activity impairment was 28.2%. Among employed patients, mean absenteeism was 4.5%, mean presenteeism was 24.9% and mean work impairment was 27.6%. In multivariable analysis, absenteeism was associated with disease duration (ß: - 0.44;95% CI: -0.80, -0.07;p=0.02)and EQ-5D (ß: -46.28; 95% CI: -89.63, -2.92; p=0.04). Presenteeism was associated with BASDAI≥4 (ß: 8.23;95% CI: 0.24, 16.22; p = 0.04), BASFI (ß: 3.59; 95% CI: 1.25, 5.92; p<0.01) and EQ-5D (ß: -64.40; 95% CI: -115.79, -13.02; p=0.02). Work impairment was associated with BASFI (ß: 3.57; 95% CI: 0.71, 6.43; p=0.02) and EQ-5D (ß: -88.00, 95% CI: -150.87, -25.13; p<0.01). Activity impairment was associated with age (ß: -0.21; 95% CI: -0.41, -0.01; p=0.04), BASDAI≥4 (ß: 19.94; 95% CI: 13.79, 26.09; p<0.01), BASFI (ß: 3.29; 95% CI: 1.63, 4.95; p<0.01), EQ-5D (ß: -82.28; 95% CI: -125.15, -39.41; p<0.01). Conclusion: Factors such as active disease, reduced physical function and poorer quality of life are associated with reduced work outcomes in patients with axSpA in Singapore. These factors need to be addressed to improve work outcomes. References: [1]Martindale, J., et al. (2015). "The impact of ankylosing spondylitis/axial spondyloarthritis on work productivity." Best Pract Res Clin Rheumatol 29(3): 512-523. [2] Ng, I. Y., et al. (2012). "Designing and implementing an evaluation of a national work support program." Eval Program Plann 35(1): 78-87 Disclosure of Interests: Yihui Goh: None declared, Yu Heng Kwan: None declared, Ying Ying Leung Grant/research support from: Abbvie, Novartis, Speakers bureau: Abbvie and Novartis, Speakers bureau: Novartis, Warren Fong : None declared, Peter Cheung: None declared